(3GdCLhHI GdeQVjI Yf GdeSGFd GdabgjIs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3eSCdI , ai GdeOHQ EPG eGJ SjOg HYOeG cGf cGJHg , hcGf bO COi HYV cJGHJg s
(3BNQgG (B:s
(3hdGjNQLg Yf YgOg eG dReg EdG GdCPi , aGYde Pdc ehabkG Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3abg GdePGgH GdCNQis